DPP4-INHIBITOR LINAGLIPTIN ACCELERATES RESOLUTION OF CRESCENT FORMATION IN A RAT MODEL OF ANTI-GBM GLOMERULONEPHRITIS - Mayer, Anna-Lena; Ebert, Nadja; Klein, Thomas; Amann, Kerstin Ute; Daniel, Christoph (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2020)
CRIS-Team WoS Importer:2020-08-21

The dipeptidyl peptidase 4 inhibitor linagliptin ameliorates renal injury and accelerated resolution in a rat model of crescentic nephritis - Mayer, Anna-Lena; Scheitacker, Iris; Ebert, Nadja; Klein, Thomas; Amann, Kerstin Ute; Daniel, Christoph (British Journal of Pharmacology, 2021)
Background and Purpose: Dipeptidyl peptidase 4 (DPP-4) inhibitors are a class of oral glucose-lowering drugs used in the treatment of type 2 diabetes. In a pilot study using human kidney biopsies, we observed high DPP-4 expression in early crescent formation. This glomerular lesion occurs in different kidney diseases and is a hallmark in the pathogenesis of renal dysfunction. Therefore, we investigated the potential involvement of DPP-4 in the pathogenesis of nephritis induced by anti-glomerular basement membrane (GBM) antibody in rats. Experimental Approach: Linagliptin and vehicle were used to treat anti-GBM nephritis in a 2- and 8-week regimen, that is either preventive or therapeutic (treatment started 7 days or 4 weeks after disease induction). Kidney function, morphologic changes, inflammation and fibrosis were monitored. Key Results: In the long-term experiment, linagliptin preventive treatment in anti-GBM nephritic rats significantly reduced the number of crescents, glomerulosclerosis, tubular injury and renal fibrosis, compared with those in untreated nephritic rats. Both linagliptin regimes significantly lowered the number of Pax8+ cells on the glomerular tuft in anti-GBM nephritis, indicating accelerated resolution of the cellular crescents. The linagliptin treatment did not change the podocyte stress in both therapeutic groups. Therapeutic intervention with linagliptin resulted in weaker amelioration of renal disease on Week 8 than did preventive intervention. Conclusion and Implications: DPP-4 inhibition with linagliptin ameliorates renal injury in a rat model of anti-GBM, indicating that linagliptin not only is a secure therapy in diabetes but also can improve resolution of glomerular injury and healing in non-diabetic renal disease.
CRIS-Team Scopus Importer:2021-02-12
Keywords: crescent formation; DPP-4 inhibitor; fibrosis; non-diabetic renal disease